Approach to students’ social representations in the construction of academic European geography: A case study of Spanish university students - Macía Arce, Xosé Carlos; Lois González, Rubén Camilo; Lestegás, Francisco Rodríguez; Armas Quintá, Francisco Xosé (Quaestiones Geographicae, 2017)
This article provides the results of classroom research involving university students training to be secondary school teachers of geography and history. The research is based on the analysis of a word association test on Europe and the European Union. The results constitute an approach to the geographical and historical representations these students have of their own European continent. This is a fundamental question considering that this collective group is training to teach the contents and values of European geography in secondary school education. From here on, our intention is no other than to carry out an exercise of synthesis and overall reflection on the test results and introduce issues which could generate some debate in the educational community.